Old but new, new but old : architectural heritage conservation - Rahman, Mahbubur, 1959-; UNESCO, Dhaka (Dhaka : UNESCO : Distributor, Omni Books, 2009)
Chiefly with reference to Bangladesh.
Includes bibliographical references.
ARC
Keywords: Historic buildings -- Conservation and restoration -- Bangladesh; Historic buildings -- Conservation and restoration; Architecture; Bangladesh